United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper examines national accounts revisions and the economic cycle for the United Kingdom. The paper concludes that upward revisions to GDP data are positively correlated with economic activity, in particular, with growth in its domestic component. The paper suggests that although revisions may have become smaller in recent years, the procyclical bias in the data revision has not been eliminated. The regression model employed also suggests that GDP growth in 1996-currently estimated at 2.4 percent-could be as much as a 0.6 percentage point higher than that estimate.